Endoscopic Biopsies and Histopathological Findings in Diagnosing Chronic Gastrointestinal Disorders in Dogs and Cats - Andrzej Rychlik; Ewa Kaczmar (Veterinary Medicine International)
Nowadays, endoscopic examination is a diagnostic tool gaining popularity in the management of gastrointestinal disorders in dogs and cats. Direct accessibility of the lumen of gastrointestinal tract combined with the mucosal biopsy provides a great diagnostic potential. Using endoscopy and endoscopically guided biopsy, one can conduct both macro- and microscopic assessment of lesions and perform many specialist adjunct examinations. Histopathological examination of mucosal biopsy specimens collected from the stomach and intestines allows us to distinguish between types of inflammations and to diagnose ulcerative, polypoid, and cancerous lesions.